Physiochemical Properties of Chitosan Biofilm for Wound Healing Applications - IDRIS, MAIZLINDA IZWANA; Muhammad Syahrul Goh, Nur Syahirah (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Chitosan is a fiber derivative from chitin, a substance found in the hard outer skeletons such as crabs, crawfish, shrimp and squid. Chitosan, a common cationic polymer is organically sustainable, biodegradable, biocompatible, non-antigenic, non-toxic, and bio functional. It may speed up the healing progression by improving the elements of inflammatory cells, macrophages, and fibroblasts. For this research project, glutaraldehyde is incorporated together to form a film for wound healing application. Solution casting method was used to fabricate the films of 1wt% dried in oven, 2wt% and 3wt% chitosan while 1wt% dried in room temperature was fabricate using pipette technique. After that, the characterization and testing that involved were Scanning Electron Microscope (SEM), Fourier Transform Infrared Spectroscopy (FTIR), Atomic Force Microscope (AFM) and contact angle measurement. SEM images showed no porosity is found, rough and uneven surfaces for films of 1wt%, 2wt% and 3wt%. FTIR spectra revealed that all films showed spectra that chitosan exist in the film. AFM results revealed that the surface roughness of chitosan films decrease with increasing amount of chitosan and film of 1wt% CS 40ml (O) recorded the highest surface roughness value. Contact angle measurements revealed that as more chitosan was introduced into homogeneous solution, the contact angle value decrease. It can be concluded that chitosan films can be applied as both hydrophilic and hydrophobic wound dressing materials.